CCD-photometry of the cataclysmic variable V2275 Cygni in 2003 - Ostrova, N. I.; Shugarov, S. Yu.; Andronov, I. L. (Одеські астрономічні публікації, 2017)
Results of CCD R-photometry of the nova V2275 Cygni obtained in summer, 2003 are reported. There are two candidate periods P = О.d46566(18) and 0d.87281(72) with corresponding amplitudes О.m180(5) and О.m174(5) and initial epochs for the maxima HJD 52825.3962(26) and HJD 2452825.3254(59)‚ respectively. At shorter time scales, the system shows the highest peak corresponding to the period 25.0572(18) minutes, semi-amplitude О.mО26(4) and initial epoch HJD Max=2452825.39846(44). The daily biases with frequencies f = 57.468 ± j may not be excluded. If this period corresponds to a coherent wave, the system may be classified as an intermediate polar with this period (or a double one 50.12 minutes).